(untitled) (Epidemiology, Biostatistics, and Public Health, 2022)
Background: Adenosine triphosphate bioluminescence produced by the firefly luciferase has been successfully introduced to verify cleaning procedures in the food industry according to the Hazard Analysis Critical Control Point program. Our aim was to evaluate the reliability of bioluminescence as a tool to monitor the effectiveness of sanitation in healthcare settings, in comparison with the microbiological gold standard. Methods: 614 surfaces of various material were randomly sampled in Policlinico University Hospital units in Palermo, Italy, to detect adenosine triphosphate bioluminescence and aerobic colony count. Linear regression model and Pearson correlation coefficient were used to estimate the relationship between the two variables of the study. Results: Aerobic colony count median was 1.71 colony forming units/cm2 (interquartile range = 3.8), whereas adenosine triphosphate median was 59.9 relative light units/cm2 (interquartile range = 128.3). Pearson coefficient R2 was 0.09. Sensitivity and specificity of bioluminescence test with respect to microbiology were 46% and 71%, whereas positive predictive value and negative predictive value were 53% and 65%, respectively. Conclusion: According to our results, there seemed to be no linear correlation between aerobic colony count and adenosine triphosphate values, suggesting that current bioluminescence technology has not any proportional relationships with culturable microbes contaminating environmental surfaces in health-care settings.